British-Qualified Accountants Outside the UK: Post-Brexit Case - Jallow, Ousman; Fanani, Zaenal; Hamidah, Hamidah (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 1 (2021)DO - 10.24843/JIAB.2021.v16.i01.p11, 2021)
This study aims to explore the impact of Brexit on the employment of accountants and auditors who already had a UK qualification. This study also assesses if they will be allowed to work outside the UK after Brexit. This study used data collected through interview and collation of previous research articles, reports magazine, and other secondary source of data. Results revealed that auditors and accountants might be potentially affected negatively by a change in their capacity to carry out audits and accounting service across borders, as the number of those who carry out such work may be quite small. This paper hopes to serve as a useful insight for stakeholder discussions, such as practitioners and standard setters, and in making decisions on strategy in the medium term and the regulation of the accountancy and audit profession post-Brexit. As the shape of Brexit becomes more explicit, the Financial Reporting Council's primary objective is to have a seamless transition and a continuation of high professional standards and a properly functioning audit and accountancy profession. Keywords: Brexit; Accountants; European Union; United Kingdom